72.9k views
4 votes
Please help 3(6x−2)=−2(4x−9)+2

2 Answers

2 votes

Answer:x=1

Step-by-step explanation: do it from both sides first

3(6x-2)=-2(4x-9)+2

3(6x-2): 18x-6

-2(4x-9)+2: -8x+20

18x-6=-8x+20

18x-6+6=-8x+20+6

18x=-8x+26

18x+8x=-8x+26+8x

26x=26

26x/26=26/26

User Kumar Mangalam
by
5.5k points
3 votes

Answer:

x=1

Explanation:

3(6x-2)=-2(4x-9)+2

3(6x-2): 18x-6

-2(4x-9)+2: -8x+20

18x-6=-8x+20

18x-6+6=-8x+20+6

18x=-8x+26

18x+8x=-8x+26+8x

26x=26

26x/26=26/26

x=1

User MhFarahani
by
6.0k points